Cross-cultural adaptation and validation of the English version of the International Index of Erectile Function (IIEF) for use in Malaysia - Lim, T O; Das, A; Rampal, S; Zaki, M; Sahabudin, R M; Rohan, M J; Isaacs, S (International journal of impotence research, 2003)
We adapted the English International Index of Erectile Function (IIEF) into Malay. This was difficult as many sex-related terms do not exist in colloquial Malay. In the pretest, there was no difficulty with comprehension and all subjects judged the Malay IIEF equivalent to the English IIEF. After slight modification, a final instrument was evaluated in two studies. Study A included 136 subjects. It showed that the instrument had good reliability and discriminant validity. The factor structure of the English IIEF was not reproducible. Study B included 26 ED subjects who underwent oral sildenafil therapy. The Malay IIEF was sensitive to treatment response. The area under the ROC curve of the Malay IIEF-5 was 0.86; the optimal cutoff score has a sensitivity of 85% and specificity of 75%. The results suggest that the Malay IIEF requires more work, but the Malay IIEF-5 has acceptable measurement properties to recommend its use in clinical practice and research.